Pengaruh Team Work dan Fasilitas Kerja terhadap Produktivitas Kerja Pegawai pada Kantor Camat Soromondi Kabupaten Bima - Muh. Gilang Ramadhan; Firmansyah Kusumayadi (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to determine the positive and significant influence of teamwork and work facilities on employee work productivity at the Soromondi District Office, Bima Regency. The instrument in this study used a questionnaire with a Likert scale. The population in this study was 58 employees consisting of 37 Civil Servants, 6 Government Employees with Work Agreements, 5 Regional Honorary Employees and 10 non-permanent employees. The sample in this study was 37 civil servants with a sampling technique used, namely purposive sampling. Data collection techniques used observation, interviews, questionnaires and documentation. Data analysis techniques used validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, determination coefficient tests, t tests and f tests with the help of SPSS version 23 for Windows. The results of the study indicate that there is a positive and significant influence of teamwork and work facilities on employee work productivity at the Soromondi District Office, Bima Regency.